Institucionalização e estratégias de legitimação da medicina alternativa e complementar - Corrêa, Rúbia Oliveira (2013)
This study addresses the Organizational Institutionalism and has as its object the micro business in Aracaju - SE in the area of complementary and alternative health. The institutionalization of organizations was analyzed from the viewpoint of its entrepreneurs, as well as the strategies of legitimation that influence the process. Regarding methodological aspects, the study is classified as exploratory, descriptive and qualitative; regarding the time dimension, the research is cross-sectional. Semi-structured interviews were applied to these entrepreneurs. The results revealed problems in conducting the companies institutionalization process, which may compromisetheir survival in the following years. According to Tolbert and Zucker s organizational model (1999), applied in this investigation, the organization institutionalization occurs through three phases: habitualization (pre-institutionalization), objectification(semi-institutionalization) and sedimentation (total institutionalization). The results showed that in most of the cases examined, the phase habitualizationhas been achieved. Concerning the stage of objectification, it is believed that companies surveyed still experience this phase, non-rationally, though. The institutional stage of sedimentation, on the other hand, was somehow impaired by groups of tough opponents and the backlog in the formal institutionalization of this sector. Thus, all companies surveyed can be framed in the semi-institutional stage; some of them still remained in the pre-institutional at the same time. It was also possible to observe the interference of positive legitimation strategies in institutionalization process. It was concluded that these strategies permeated all phases of the institutionalization process as suggested by the model used in the research.